Potential of E-Commerce as a Method of Agricultural Business Marketing on MSME Scale - Gede Endra Bratha, Wayan; Tussoleha Rony, Zahara; Winarso, Widi (Dinasti Publisher, 2022)
The study aims to review the performance of e-commerce in the operation of agricultural SMEs so that the view for developing and implementing e-commerce can be improved. The method used in this research is an approach is carried out through the literature study, namely research that critically examines knowledge, ideas or findings and provides theoretical and methodological contributions to the object of study. Originality/value – This study identifies, explores, analyzes and summarizes the main themes that contribute to deepening the literature by identifying the potential of e-commerce as a marketing method for agricultural businesses MSME scale.